2020
DOI: 10.1186/s43058-020-00055-z
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for colorectal cancer screening in a low-income urban community in Mexico City

Abstract: Background: Colorectal cancer (CRC) incidence and mortality are increasing in many low-and middle-income countries (LMICs), possibly due to a combination of changing lifestyles and improved healthcare infrastructure to facilitate diagnosis. Unfortunately, a large proportion of CRC cases in these countries remain undiagnosed or are diagnosed at advanced stages, resulting in poor outcomes. Decreasing mortality trends in HICs are likely due to evidence-based screening and treatment approaches that are not widely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
13
0
2
Order By: Relevance
“…Poverty has long been a barrier to CRC screening, especially in countries with limited resources. Patients are unlikely to seek out preventative services when they are unable to fulfill their basic needs[ 26 ]. The effects of the pandemic are likely to worsen these barriers and result in further decreases in screening in these populations.…”
Section: Barriers To Crc Screening Due To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty has long been a barrier to CRC screening, especially in countries with limited resources. Patients are unlikely to seek out preventative services when they are unable to fulfill their basic needs[ 26 ]. The effects of the pandemic are likely to worsen these barriers and result in further decreases in screening in these populations.…”
Section: Barriers To Crc Screening Due To Covid-19mentioning
confidence: 99%
“…Regarding colonoscopies for these patients, grassroot advocacy programs are encouraged to generate a list of community gastroenterologists to provide colonoscopies to CHC patients[ 79 ]. A qualitative study from Mexico shows that implementation of screening programs that offer FIT and colonoscopy at no cost would greatly increase CRC screening participation[ 26 ]. To alleviate knowledge gaps in patients, existing platforms should provide information about COVID-19 and extend CRC awareness throughout the year[ 78 ].…”
Section: Exacerbations Of Crc Inequities Due To Covid-19mentioning
confidence: 99%
“…This may reflect poor health education about CRC signs and symptoms in Arab countries and underline the need for establishing continuous educational programs. Another contributing factor could be the shared, misleading cultural beliefs in these countries [ 52 ]. A living example of this was noticed during the data collection for this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Denmark showed that cancer was perceived as a terminal illness that cannot be treated and screening was only relevant for symptomatic patients [ 53 ]. The hopelessness and helplessness people feel towards CRC could be the result of their poor insight—healthcare illiteracy—towards the role of early detection in the morbidity and mortality of the disease [ 52 ]. Thus, a multidisciplinary approach should be considered to raise the public awareness about the importance of early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had deficient knowledge of CRC risk factors, clinical symptoms, and detection would be discouraged from attending screening. So, implementation of educational interventions on the part of participants and staff of the primary healthcare system for removing barriers to CRC knowledge was quite essential, as it has already been proved to be a successful facilitator of CRC screening [ 48 ].…”
Section: Discussionmentioning
confidence: 99%